(untitled) (Research, Society and Development, 2020)
The objective of this work is to identify the predominant learning styles of students in an integrated technical course, as well as to analyze the changes in these styles due to being in the first, second or third year of the course. Thus, the reference for driving was based on Felder and Silverman (1988). The authors indicate that students learn in different ways as seeing and listening, reflecting and acting, by logical reasoning and intuition, visualizing and memorizing, building analogies and mathematical models, constantly and in stages. A qualitative and quantitative perspective was adopted for data analysis. Regarding the techniques used for data collection, a questionnaire was applied to students. It was found that students identify with visual/verbal aspects, have a greater preference for images and diagrams in the three years of the analyzed course. In general, students have linear reasoning.